A Prooxidant and an Antioxidant Sow’s Status with Hepathopathy - Piatrouski, Sergey; Hlebus, Natali (ՀԱԱՀ հիմնադրամ)
The role of lipid peroxidation in the pathogenesis of liver diseases in sows was studied. The state of the antioxidant system in these diseases was also assessed. The liver of sows has been examined after slaughter. There were four groups formed: healthy, acute and chronic hepatosis (HS), and liver cirrhosis. An increase in the level of endogenous intoxication has established, the content of primary (diene conjugates), secondary (malondialdehyde, ketodienes, ketotrienes), and final (Schiff base) products of lipid peroxidation in the blood of sows with hepatopathy. Also noticed that sows with hepatopathy had decreased antioxidant protection, catalase activity, and concentration of tocopherol and ascorbic acid. The level of change was growing with a gravity of hepatopathy. The most expressed disturbance has been observed in sows with liver cirrhosis.
Keywords: Veterinary Science and Animal Breeding